CGIAR Road from COP29 to COP30 Webinar Series #2: The New Collective Quantified Goal (NCQG) - CGIAR Science Program on Climate Action (2025)
Following the first fireside chat in this series, which examined Article 6.8 and the role of non-market approaches in global climate action (recap available here), this second session will explore a significant finance outcome from COP29 in Baku—the agreement on a New Collective Quantified Goal (NCQG) for climate finance. CGIAR has been actively engaged in the NCQG negotiations, contributing formal submissions and closely monitoring developments at COP29. A summary of the discussions and outcomes can be found here.